ANALISIS YURIDIS PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 TENTANG PENYELESAIAN BATASAN TINDAK PIDANA RINGAN DAN PENYESUAIAN PIDANA DENDA DALAM KUHP - , SENTOT KUNTO WIBOWO SH; , Sigit Riyanto, S.H, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of the study, this research is to find answers to two related questions about the Juridical Analysis of Supreme Court Regulation No. 2 Year 2012 About the Settlement Limits Lightweight Crime And Criminal Penalties Adjustment In the Criminal Code, namely: First, what is the position of Supreme Court Regulation No. 2 of 2012 on Settlement Limitation Crime Lightweight (tipiring) of the Criminal Code and Criminal Penalties under the Act No. 12 Year 2011 on the Establishment Regulation Legislation? Secondly, whether the factors that hinder enforcement of the Supreme Court Regulation No. 2 of 2012 on the Settlement Limits Crime Lightweight (tipiring) and Criminal Penalties in the Criminal Code? The research method, this research is a method of normative research, research that is based on library research to obtain secondary data in the field of law. The location was used as a place of research is the University of Indonesia, Jakarta, Yogyakarta GMU Library, and the Library of the School of Police - PTIK Jakarta. Research, based on data analysis of the results, it can be concluded: First, the Supreme Court as an institution authorized by the state high of Law No. 12 Year 2011 on the Establishment Regulation Legislation to establish a Rule of the Supreme Court under Article 101 of the law. The authority was reinforced in Law No. 5 of 2004 as amended by Act No. 3 of 2009 on the Supreme Court. Position Perma not violate the law. But the need for improved effectiveness Perma remember it applies to the inside or external level so that the necessary legislation to streamline government regulation limits the usability of minor criminal offenses and penalties. Second, the MA can submit a review to the Constitutional Court yudicial related articles of the Criminal Code that generate inequality that crime to the value of the goods under Rp. 2,500,000, can be tipiring.